Current advances in transdermal delivery of drugs for Alzheimer's disease - Nguyen, Thuy Trang (Indian J Pharmacol, 2017)
Alzheimer's disease (AD) is a common, progressive, fatal neurodegenerative disorder, which will play an increasingly important role both socially and financially in the aging populations. Treatments for AD show modest improvements in cognition and global functioning among patients. Furthermore, the oral administration of treating AD has had some drawbacks that decrease the medication adherence and efficacy of the therapy. Transdermal drugs are proposed as an alternative remedy to overcome the disadvantages of current pharmaceutical dosage options for this chronic disorder. They could have different strengths, such as offering a stable diffusion of active substance, avoiding the first pass metabolism, and reducing system adverse reactions. This article reviews the technical principles, novel techniques of transdermal delivery drug, and prospects for future development for the management of cognitive and behavioral dysfunctions in AD patients.